2022
DOI: 10.1016/j.chom.2021.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Pre-existing humoral immunity to human common cold coronaviruses negatively impacts the protective SARS-CoV-2 antibody response

Abstract: SARS-CoV-2 infection causes diverse outcomes ranging from asymptomatic infection to respiratory distress and death. A major unresolved question is whether prior immunity to endemic, human common cold coronaviruses (hCCCoV) impacts susceptibility to SARS-CoV-2 infection or immunity following infection and vaccination. Therefore, we analyzed samples from the same individuals before and after SARS-CoV-2 infection or vaccination. We found hCCCoV antibody levels increase after SARS-CoV-2 exposure, demonstrating cro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
65
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(84 citation statements)
references
References 56 publications
(73 reference statements)
8
65
0
Order By: Relevance
“…We found that while everybody had detectable antibody titers to CCC individuals varied in the level of T cell reactivity (possibly as a function of recent exposure, HLA type or other individual and environmental factors), and that the subjects with high CCC T cell reactivity, but not antibody titers, are those most likely to be associated with pre-existing SARS-CoV-2 immune reactivity. This is consistent with findings that CCC antibodies might not protect against SARS-CoV-2 infection or disease severity 24,50 but T cells do 30,51 .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…We found that while everybody had detectable antibody titers to CCC individuals varied in the level of T cell reactivity (possibly as a function of recent exposure, HLA type or other individual and environmental factors), and that the subjects with high CCC T cell reactivity, but not antibody titers, are those most likely to be associated with pre-existing SARS-CoV-2 immune reactivity. This is consistent with findings that CCC antibodies might not protect against SARS-CoV-2 infection or disease severity 24,50 but T cells do 30,51 .…”
Section: Discussionsupporting
confidence: 91%
“…Some discrepancies may be reconciled as some reports consider immunity as protection from re-infection while others consider protection from symptomatic disease. CCC infections are associated with generation of antibody titers widely detectable in the human population 17,[23][24][25] . However, little data is available regarding the frequency of memory T cell responses against CCC, and in particular their stability overtime.…”
Section: Introductionmentioning
confidence: 99%
“…The original antigenic sin hypothesis suggests that preexisting immunity results in the reactivation of a response to an earlier strain, as opposed to the formation of an unbiased response against the current strain. While this recall could offer temporal advantages, it may reduce the formation of neutralizing antibodies, thereby dampening effective clearance of the novel virus, as has recently been reported in mouse models ( Lapp et al, 2021 ; Lin et al, 2022 ). Seminal studies of responses to influenza, based on epidemiology, modeling, and repertoire profiling, suggest that the antibodies generated from childhood exposure to influenza are ‘imprinted’ and exert a major influence on the nature of the antibody response elicited upon subsequent exposures in humans ( Francis et al, 1947 ; Fonville et al, 2014 ; Kucharski et al, 2015 ; Gostic et al, 2016 ; Lee et al, 2019 ).…”
Section: Discussionmentioning
confidence: 98%
“…Likewise, while both vaccination cohorts showed an absence of or reduction in boosting of cross-reactive responses, whether this absence is beneficial or detrimental cannot be determined from the data presented here. While some studies of natural infection have suggested that these boosted responses are not associated with protection, but instead with more severe disease ( Guo et al, 2021 ; Aydillo et al, 2021 ; Dugan et al, 2021 ; Lin et al, 2022 ; Anderson et al, 2021 ; Gombar et al, 2021 ), others have supported the opposite conclusion ( Aran et al, 2020 ; Dugas et al, 2021a ; Dugas et al, 2021b ). Collectively, these natural infection studies are challenged by the inability to distinguish between correlation and causation, and to separate contributions from humoral from cellular memory.…”
Section: Discussionmentioning
confidence: 99%
“…Future work will address the mechanism of binding of VN and CLU to coronavirus infected cells, as well as unanswered questions such as how widespread this mechanism is among circulating and pathogenic coronaviruses, which viral components are needed for recruitment, investigating individual serum donors and VN and CLU recruitment, and the correlation between anti-coronavirus antibodies from infection versus vaccination in outcomes from infections. Interestingly, pre-existing antibodies to circulating coronaviruses were negatively correlated with SARS-CoV-2 susceptibility and disease progression [54,55]. Future work will determine if VN and CLU are recruited to SARS-CoV-2 infected cells in an antibody-dependent manner and if OC43-specific antibodies can recognize SARS-CoV-2 infected cells and aid in VN and CLU recruitment.…”
Section: Discussionmentioning
confidence: 95%